Implementasi Asas-asas Hukum dalam Pembentukan Peraturan Desa yang Baik di Kabupaten Polewali Mandar dan Kabupaten Majene Provinsi Sulawesi Barat - Putera Astomo; Pahruddin Pahruddin (Universitas Teuku Umar, 2020)
The Draft Village Regulations/Village Regulations as a village legal product specifically governing the Village APB, fees, spatial planning, and Village Government organizations must be supervised. The authority to supervise is given by Law Number 6 of 2014 on Villages to the Regent/Mayor. This village legal product has the potential to be canceled by the Regent/Mayor if it conflicts with higher statutory legislations or the public interest. This means that conflicting village legal products cause problems in the formation process that is not compliant with law principles in the formation of legislations. The activities carried out consisted of three stages. First, the preparation stage invites the village head and his staff, BPD, and community leaders in the village office. Second, the implementation phase presented the implementation of law principles in the formation of village regulations to them at the village office. Third, the stage of providing recommendations to the village head and his staff and BPD related to Village Regulations that are in accordance or not with the law principles in the formation of legislations. The findings of the village regulations that have been evaluated and analyzed includes: Village Regulations Simbang Number 1 of 2012 on Village Income and Wealth Sources, Village Regulations Simbang Number 03 of 2018 on Village Government Work Plan (RKP Village) Fiscal Years 2019, Village Regulations Tinambung Number 09 of 2018 on Village Income and Expenditure Budget Fiscal Years 2019, and Village Regulations Tangan Baru Number 01 of 2018 on Prohibition of Defecation at Random.Keywords: Law Principles, Village Regulations, Legislation